Subjective sleep complaints and their effect on glycaemic control in adult type 2 diabetics - Mathole, Garrison Phutiana (My University, 2018)
There is emerging evidence that suggest that sleep disorders are a novel risk factor for diabetes and poor glycaemic control but no data exists for South African populations Objectives: To describe the prevalence of subjective sleep complaints in adult type 2 diabetics in Chris Hani Baragwanath academic hospital in Soweto and to examine the association between subjective sleep complaints and glycaemic control. Patients and methods: A cross sectional study, with 150 adult participants attending a diabetic clinic at Chris Hani Baragwanath hospital. A variety of short validated sleep questionnaires including insomnia severity index (ISI) were used. Results: More patients (46%) in the group with poor glycaemic control had insomnia compared to only 21.6% in the controlled group (p = 0.014). The uncontrolled group had a higher Insomnia (ISI) score of 14 compared to the controlled group with (score of 8) (p = 0.008). The prevalence of other sleep disorders was high but not significantly related to poor glycaemic control. Conclusion: There is a high prevalence of sleep disorders in diabetics and insomnia is significantly associated with poor glycaemic control
A Research project submitted in part fulfillment for the Degree of Master of Medicine in Internal Medicine, to the Faculty of Health Sciences, Department of Internal Medicine, University of the Witwatersrand Johannesburg 2018